6′-Hydroxy Justicidin B Triggers a Critical Imbalance in Ca2+ Homeostasis and Mitochondrion-Dependent Cell Death in Human Leukemia K562 Cells - Luo, Jiaoyang; Qin, Jiaan; Fu, Yanwei; Zhang, Shanshan; Zhang, Xingguo; Yang, Meihua (Frontiers in Pharmacology, 2018)
Justicia procumbens (J. procumbens) is a traditional Chinese herbal medicine which was used for the treatment of fever, pain, and cancer. A compound 6’-hydroxy justicidin B (HJB) isolated from J. procumbens exhibits promising biological properties. However, the mechanism of action and the in vivo behavior of HJB remain to be elucidated. In this study, we investigated the mechanism of action of HJB on human leukemia K562 cells and its pharmacokinetic properties in rats. The results demonstrated that HJB significantly inhibited the proliferation of K562 cells and promoted apoptosis. Besides, HJB resulted in decreased mitochondrial membrane potential deltaPSIm, increased the level of the calcium homeostasis regulator protein TRPC6 and cytosolic calcium. The activity of caspase-8, caspase-9 and the expression of p53 were significantly increased after treatment with HJB. Additionally, HJB has rapid absorption rate and relative long elimination t1/2, indicating a longer residence time in vivo. The results indicate that HJB inhibited the proliferation of K562 cells and induced apoptosis by affecting the function of mitochondria and calcium homeostasis to activate the p53 signaling pathway. The pharmacokinetic study of HJB suggested it is absorbed well and has moderate metabolism in vivo. These results present HJB as a potential novel alternative to standard human leukemia therapies.